Gabonese presidential election of 2016 : contribution to a problematic of democratic construction in Francophone Africa - (:unkn) unknown (My University, 2022)
On August 27th, Gabon has organized for the fifth time since 1990, year of adoption of the return of the pluralism system, a presidential election on a backdrop of intense tensions. This election opposed several candidates. But of all in the running, only those said to be "major", in particular Ali Bongo Ondimba, outgoing president and candidate of the Gabonese Democratic Party (PDG) in power since 1968 and Jean Ping, former baron of the regime who spent in the opposition and by elsewhere, former President of the Commission of the African Union (AU) have attracted attention. After a lively and very controversial electoral dispute, it was finally Ali Bongo Ondimba who was elected President for a second term of seven years. Unlike previous electoral processes, the decision of the Constitutional Court failing to bring serenity to the country, instead plunged it into an unprecedented crisis which on one hand affected living together and on the other hand did not allow democratic consolidation in Gabon.
Keywords: African Research